MENINGKATKAN MINAT BACA ANAK TERHADAP AL QUR’AN MELALUI METODE WAFA (Studi pada Siswa SDN Pengkol 1 Kecamatan Mantingan) - Riza Fahruddin; Darmanto Darmanto (LPPM STAI Muhammadiyah Probolinggo, 2022)
The Qur'an is the holy book of Muslims which was revealed by Allah to the Prophet Muhammad shalallahu 'alaihi wa sallam through the intermediary of the angel Gabriel. Talking about the Qur'an today, there are still people who can't read fluently or even can't read it at all. This is due to a lack of interest in studying the Qur'an more deeply. In addition, time constraints are the cause of the lack of studying the Qur'an. On the other hand, there are phenomena in the school environment such as students who do not yet have a love for the Qur'an. To overcome this is to pay attention to methods that are appropriate for their age level. This study aims to (1) determine the learning of the Qur'an using the wafa method at SDN Pengkol 1 mantingan Ngawi, (2) to determine the advantages and disadvantages of the wafa method. This study uses a qualitative description. The results of the research and discussion show that studying the Qur'an with the Wafa method is very suitable and fun with maximum results. Although, besides the wafa method, there are other methods that are much more varied. However, the results of implementing this wafa method make it easier for children to learn and memorize the Qur'an